Synthesis of enriched boron nitride nanocrystals: A potential element for biomedical applications - Ahmad, P.; Khandaker, Mayeen Uddin *; Muhammad, N.; Rehman, F.; Ullah, Z.; Khan, G.; Khan, M. I.; Haq, S.; Ali, H.; Khan, A.; Saeed, Y.; Irshad, M. I. (Elsevier, 2020)
The shortcomings in Boron neutron capture therapy (BNCT) and Hyperthermia for killing the tumor cell desired for the synthesis of a new kind of material suitable to be first used in BNCT and later on enable the conditions for Hyperthermia to destroy the tumor cell. The desire led to the synthesis of large band gap semiconductor nano-size Boron-10 enriched crystals of hexagonal boron nitride (10BNNCs). The contents of 10BNNCs are analyzed with the help of x-ray photoelectron spectroscopy (XPS) and counter checked with Raman and XRD. The 10B-contents in 10BNNCs produce 7Li and 4He nuclei. A Part of the 7Li and 4He particles released in the cell is allowed to kill the tumor (via BNCT) whereas the rest produce electron-hole pairs in the semiconductor layer of 10BNNCs suggested to work in Hyperthermia with an externally applied field.